An approach for Schools Management System on The Cloud Computing - Bashir, Murtada Khalafallah; Biraima, Abdulrhman Mohammed Elhassan; Babikir, Gais Alhadi (Gezira Journal of Engineering and Applied Sciences, 2018)
The schools management information system plays an essential role for the success of the school management. The main purpose of the management information system at initial steps of its development is to improve the efficiency of the office activities. In school environment it was used to store student and personnel data. The most concern was being focused on data entry and collation, rather than on data transfer or analysis. This paper proposed a framework based on cloud computing that provides detailed and summarized information on the critical areas of the management activities to guide schools administrators in planning and in decision-making. Such information system will be accessible anywhere anytime as data are stored in remote servers that are accessible to users over the internet. Unified Modeling Language (UML) is used in the development of the proposed framework. To evaluate the developed framework, a web based application was developed using the proposed framework, and then some International Organization for Standardization (ISO) qualification metrics were used to evaluate the developed web based application using some selected characteristics. The evaluation results show that the proposed framework is very effective. Through the evaluation, the proposed framework is found to represents a solution to most of the problems mentioned in the previous researches and this implies that the proposed framework can be adopted by schools for more efficient information management and more effective management decisions.